English in online dating: Analysing language use on Grindr’s “About me” section in Pampanga - Ezekiel Espinosa; Rodolfo P Dizon Jr (Yayasan Mitra Persada Nusantara, 2026)
With the growing population and increasing visibility of the gay community, platforms such as Grindr have become crucial spaces for Filipino gay men to explore and connect; however, existing studies largely focus on hook-up culture, thereby overlooking how users construct identity through language. Thus, this study examined how Filipino gay men use their Grindr's “About Me” section to perform identity and navigate stigma in the Philippines. Situated within digital linguistics and queer studies, the research analyses ninety publicly visible Grindr profiles from Angeles City, Pampanga. Specifically, it was guided by Corpus Linguistics and Nguyen-Trung Kien’s Digital Dramaturgical Model, employing a qualitative, exploratory design through purposive sampling and corpus-based Thematic Analysis. In particular, linguistic features were examined across three categories: (1) words and phrases, (2) acronyms and slang, and (3) emojis. The findings revealed recurring lexical patterns emphasizing discretion, masculinity, sexual roles, health, and immediacy. While acronyms and slang function as efficient subcultural codes for expressing preferences and boundaries, Emojis serve as paralinguistic cues that convey affect and intent. Consequently, these linguistic strategies reflect forms of impression management shaped by platform constraints, sociocultural stigma, and local norms. The study demonstrates that Grindr profiles serve as digital front-stage performances where users negotiate visibility, desirability, and safety, thereby offering localized insight into how Filipino gay men strategically use language to construct identity within a conservative, postcolonial, and multilingual context.